2020
DOI: 10.1080/19490976.2020.1832857
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine improves gut barrier integrity and gut microbiota function in diet-induced obese mice

Abstract: Obesity is associated with impaired intestinal barrier function and dysbiosis of the gut microbiota. Spermidine, a polyamine that acts as an autophagy inducer, has important benefits in patients with aging-associated diseases and metabolic dysfunction. However, the mechanism of spermidine on obesity remains unclear. Here, we show that spermidine intake is negatively correlated with obesity in both humans and mice. Spermidine supplementation causes a significant loss of weight and improves insulin resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
252
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(271 citation statements)
references
References 52 publications
(70 reference statements)
15
252
2
2
Order By: Relevance
“…Polyamines constitute major products of the colonic microbiota, as shown after oral administration of the immunogenic commensal A. muciniphila [ 43 ]. Polyamines can improve the intestinal barrier function [ 44 ] and cancer immune-surveillance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines constitute major products of the colonic microbiota, as shown after oral administration of the immunogenic commensal A. muciniphila [ 43 ]. Polyamines can improve the intestinal barrier function [ 44 ] and cancer immune-surveillance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional uptake of polyamines has been correlated with reduced mortality from cancer and cardiovascular disease in two independent population studies [ 36 , 37 ]. Moreover, in mice, spermidine improve the gut barrier function [ 38 ] and has marked antiobesity, antidiabetic and cancer immunosurveillance-improving effects [ 39 41 ]. These effects of polyamines are due to the induction of autophagy in host cells [ 40 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the abundance of luminal polyamines is positively correlated with longevity in mice 5 . Likewise, exogenous spermidine administration extends the lifespan in model organisms and improves cardiac dysfunction as well as metabolic syndrome in mice by inducing autophagy [6][7][8] . Furthermore, the enhancement of luminal putrescine production by administration of probiotics and arginine improved reactive hyperaemia index representing endothelial function in randomised controlled clinical trial 9 .…”
mentioning
confidence: 99%